Swept Source Optical Coherence Tomography Angiography for Contact Lens-Related Corneal Vascularization - Marcus Ang; Yijun Cai; Anna C. S. Tan (Journal of Ophthalmology)
Purpose. To describe a novel technique of adapting a swept-source optical coherence tomography angiography (OCTA) to image corneal vascularization. Methods. In this pilot cross-sectional study, we obtained 3 × 3 mm scans, where 100,000 A-scans are acquired per second with optical axial resolution of 8 μm and lateral resolution of 20 μm. This was performed with manual “XYZ” focus without the anterior segment lens, until the focus of the corneoscleral surface was clearly seen and the vessels of interest were in focus on the corresponding red-free image. En face scans were evaluated based on image quality score and repeatability. Results. We analyzed scans from 10 eyes (10 patients) with corneal vascularization secondary to contact lens use in 4 quadrants, with substantial repeatability of scans in all quadrants (mean image quality score 2.7 ± 0.7; κ=0.75). There was no significant difference in image quality scores comparing quadrants (superior temporal: 2.9 ± 0.6, superior nasal: 2.8 ± 0.4, inferior temporal: 2.5 ± 0.9, and inferior nasal: 2.4 ± 1.0; P=0.276) and able to differentiate deep and superficial corneal vascularization. Conclusion. This early clinical study suggests that the swept-source OCTA used may be useful for examining corneal vascularization, which may have potential for clinical applications such as detecting early limbal stem cell damage.